Changing the paradigm of disability from stigma to equity in university social work education in Kyrgyzstan. (17th January 2020) - Katsui, Hisayo; Kazakunova, Gulmira; Mojtahedi, Mina C.
Summary: The main aim of this paper is to tease out the historical and deeply rooted ethical standards, spirituality, and social values that have long supported the social service system in Kyrgyzstan, which, today, faces pressure to align with the United Nations Convention on the Rights of Persons with Disabilities. The data are based on an intervention conducted as part of the European Union‐Social Protection Systems programme in Kyrgyzstan between 2017 and 2018 where 30 university lecturers were part of. Interviews both to the Kyrgyz trainers with disabilities and to the trainees of the university lecturers as well as follow‐up survey conducted in 2019 form important part of data for this paper. We first investigate the conventional ethical standards, spiritual explanations, and social values related to disabilities within the Kyrgyz social protection system and social services. We elaborate on the Kyrgyz context of the societal ethics, spirituality, and values around disability in the Kyrgyz university education for social workers. Second, we analyse the transformation of the perception of disability among the university lecturers. We conclude this paper with a discussion on the negotiation between a charity‐based approach that reinforces the stigmatization of disability and a human rights‐based approach that promotes paradigm change, to contribute to global discourse of social change towards disability inclusion.